Organic material with balanced C‐nutrient stoichiometry and P addition could improve soil P availability with low C cost. Issue 5 (27th September 2021) - Fei, Chao; Zhang, Shirong; Feng, Xionghan; Ding, Xiaodong
Abstract: Background: Carbon (C) addition to promote phosphorus (P) turnover by microbes is recommended to increase soil P availability. The C‐nutrient stoichiometry of organic materials (OM) are the primary factors in controlling soil P availability and C storage. Methods: A pot experiment was carried out to investigate the effects of different organic matter (OM) with equal carbon input [soybean dregs (SD), chicken manure (CM), and vermicompost (VC), 1000 mg C kg –1 soil] under three P levels (0, 10, and 20 mg P per kg dry soil) on soil P availability, C content, and plant growth in high P fixing soils. Results: Plant biomass and shoot P content were significantly increased in P and OM addition treatment. Application of OM or P alone had no effect on soil available P (AP) but increased the microbial P (MBP). Compared with P addition alone, soil potential AP pool (the sum of soil AP and MBP content) was increased by 89%–200% in both OM and P addition soil. Soil potential AP pool and dissolved organic carbon (DOC) in VC treatment were significantly increased compared with those in CM and SD treatments. On day 60, compared with VC treatment, SD and VC treatments significantly increased alkaline phosphatase (ALP) but decreased soil organic carbon (SOC) content, in which ALP was negatively correlated with SOC and net C balance. Conclusion: A small amount of P and vermicompost addition, which had a balanced carbon‐nutrient stoichiometric ratio, was an effective measurement in improving soil AP pool and C content in P‐fixing soil.